Chains - Anderson, Laurie Halse (New York : Simon & Schuster Books for Young Readers, 2008)
After being sold to a cruel couple in New York City, a slave named Isabel spies for the rebels during the Revolutionary War.
"Seeds of America.".
Booklist starred.
Library Media Connection starred.
School Library Journal.
5.2
5-8
Keywords: African Americans -- Juvenile fiction; Slavery -- Juvenile fiction; African Americans -- Fiction; Historical fiction; Slavery -- Fiction; Spies -- Fiction; African Americans -- Fiction; Historical fiction; Slavery -- Fiction; Spy stories; New York (N.Y.) -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; New York (N.Y.) -- History -- Revolution, 1775-1783 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; New York (N.Y.) -- History -- Fiction; United States -- History -- 1775-1783, Revolution -- Fiction; Historical fiction; Spy stories